Pregunta
upstudy study bank question image url

\( (x+2)^{\frac{1}{2}}=x \) What is the solution to the given equation?

Ask by Morrison Bond. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

The solution to the equation \( \sqrt{x + 2} = x \) is \( x = 2 \).

Solución

To solve the equation: \[ \sqrt{x + 2} = x \] **Step 1: Determine the Domain** The square root function requires the argument to be non-negative: \[ x + 2 \geq 0 \implies x \geq -2 \] Additionally, since \(\sqrt{x + 2} = x\) and the square root is always non-negative, \(x\) must also satisfy: \[ x \geq 0 \] So, the domain of the equation is \(x \geq 0\). **Step 2: Square Both Sides** To eliminate the square root, square both sides of the equation: \[ (\sqrt{x + 2})^2 = x^2 \implies x + 2 = x^2 \] **Step 3: Rearrange the Equation** Bring all terms to one side to form a quadratic equation: \[ x^2 - x - 2 = 0 \] **Step 4: Solve the Quadratic Equation** Use the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] For the equation \(x^2 - x - 2 = 0\), \(a = 1\), \(b = -1\), and \(c = -2\). Plugging these in: \[ x = \frac{-(-1) \pm \sqrt{(-1)^2 - 4(1)(-2)}}{2(1)} = \frac{1 \pm \sqrt{1 + 8}}{2} = \frac{1 \pm 3}{2} \] This gives two potential solutions: \[ x = \frac{1 + 3}{2} = 2 \quad \text{and} \quad x = \frac{1 - 3}{2} = -1 \] **Step 5: Verify the Solutions** Recall the domain \(x \geq 0\): - \(x = 2\) is valid. - \(x = -1\) is **not** valid since it doesn't satisfy \(x \geq 0\). **Conclusion** The only real solution to the equation is: \[ \boxed{2} \]

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the equation \( (x+2)^{\frac{1}{2}}=x \), first, square both sides to eliminate the square root, yielding \( x + 2 = x^2 \). Rearranging this gives the quadratic equation \( x^2 - x - 2 = 0 \). Factoring, we find \( (x - 2)(x + 1) = 0 \), giving solutions \( x = 2 \) and \( x = -1 \). However, we must check these in the original equation due to potential extraneous solutions. When substituting \( x = 2 \), we find \( (2+2)^{\frac{1}{2}} = 2 \), which holds true. For \( x = -1 \), \( (-1+2)^{\frac{1}{2}} = 1 \), which does not equal \(-1\). Thus, the only valid solution is \( x = 2 \). In summary, the solution is \( x = 2 \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad